Проявления скрытого сакрального порядка в творчестве Достоевского: (К вопросу о двойной реальности в романе Ф.М. Достоевского «Преступление и наказание») - БЯНЬГЭ, ЧЖАН (SlavVaria, 2021)
The Manifestation of Divine Order in Dostoevsky’s Work: On Dual Reality in Crime and Punishment and Bakhtin’s Carnivalesque Poetics. At the plot level of the novel, the core drive of promoting the development of incidents and fates of characters is a continued rising spiritual movement: a process of spiritual resurgence of man experiencing death and resurrection. This article discusses the development process of this divine order, which run through the plots and echoed in all details.